2016
DOI: 10.1007/s00125-016-4101-6
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum magnesium associated with SGLT2 inhibitor use in type 2 diabetes patients: a meta-analysis of randomised controlled trials

Abstract: Aims/hypothesis By analysing available evidence from randomised controlled trials (RCTs), we aimed to examine whether and to what extent sodium-glucose cotransporter 2 (SGLT2) inhibitors affect serum electrolyte levels in type 2 diabetes patients. Methods We searched PubMed, EMBASE, Cochrane Central Register of Controlled Trials (CENTRAL) a nd ClinicalTrials.gov up to 24 May 2016 for published RCTs of SGLT2 inhibitors that reported changes in serum electrolyte levels. Weighted mean differences (WMD) between ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
103
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(118 citation statements)
references
References 28 publications
(30 reference statements)
12
103
0
3
Order By: Relevance
“…17 Newer antidiabetic agent, sodium-glucose co-transporter 2 (SGLT2) inhibitors have been reported to increase serum Mg level in diabetic patients. 25 Most studies related to serum Mg and diabetes were done among diagnosed diabetic patients. Half of type 2 diabetic patients remain undetected and one-third to half of type 2 diabetic patients have one or more complications during diabetes diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…17 Newer antidiabetic agent, sodium-glucose co-transporter 2 (SGLT2) inhibitors have been reported to increase serum Mg level in diabetic patients. 25 Most studies related to serum Mg and diabetes were done among diagnosed diabetic patients. Half of type 2 diabetic patients remain undetected and one-third to half of type 2 diabetic patients have one or more complications during diabetes diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that serum magnesium (Mg) increased by 0.07 - 0.18 mEq/L after the start of treatment with SGLT2 inhibitors [3, 4]. The EMPA-REG OUTCOME study also showed that serum Mg increased from 1.7 to 1.8 mEq/L [1].…”
Section: To the Editormentioning
confidence: 99%
“…Previous studies have demonstrated elevation of the serum Mg concentrations after the initiation of SGLT-2 inhibitor treatment [12]. We recently suggested that the increase of the serum Mg level associated with SGLT2 inhibitor treatment could explain, at least in part, the reduction of the CV risk observed in the EMPA-REG OUTCOME study [13], because, as mentioned above, hypomagnesemia increases the risk of CV events.…”
Section: Mg Concentration Increases With Sglt2 Inhibitor Treatmentmentioning
confidence: 84%
“…This rapid effect of the drug is difficult to explain based on the beneficial effects of empagliflozin on the glucose and lipid metabolism alone, which are of much slower onset. Various hypotheses have been proposed, and while the precise mechanism(s) remain unknown, the ketone body hypothesis and hematocrit hypothesis have attracted the most attention [11].Previous studies have demonstrated elevation of the serum Mg concentrations after the initiation of SGLT-2 inhibitor treatment [12]. We recently suggested that the increase of the serum Mg level associated with SGLT2 inhibitor treatment could explain, at least in part, the reduction of the CV risk observed in the EMPA-REG OUTCOME study [13], because, as mentioned above, hypomagnesemia increases the risk of CV events.…”
mentioning
confidence: 99%